2021
DOI: 10.3390/healthcare9101399
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Symptoms: What Not to Be Overlooked When Approaching Suicidal Ideation among University Students

Abstract: Suicidal ideation is a serious condition antecedent to suicidal attempts and is highly related not only to depression but also other psychosocial factors. This study aimed to examine the predictive effects of these potential factors for suicidal ideation among young adult university students. A cross-sectional survey was conducted on a sample of university students in Thailand. An online questionnaire employed the perceived stress scale-10 (PSS-10), the patient health questionnaire-8 (PHQ-8), the multidimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…It has been found that the suicide rate among people with BPD may be as high as 10%, which is almost 50 times higher than those of the general population [ 1 ]. BPD was found to be higher than depressive symptoms in predicting suicidality among Thai university students, (OR 1.19 vs. 1.16) [ 5 ]. This finding was in line with a study among Thai adults in which BPD showed a higher predicting effect for suicidal attempts than depressive disorders (OR 8.439 vs. 4.62) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the suicide rate among people with BPD may be as high as 10%, which is almost 50 times higher than those of the general population [ 1 ]. BPD was found to be higher than depressive symptoms in predicting suicidality among Thai university students, (OR 1.19 vs. 1.16) [ 5 ]. This finding was in line with a study among Thai adults in which BPD showed a higher predicting effect for suicidal attempts than depressive disorders (OR 8.439 vs. 4.62) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this methodological choice was made in order to measure knowledge during all stages of the intervention, it may have contributed to participants dropping out of the intervention, since many students did not complete the questionnaire in the post-intervention and follow-up phases and therefore gave up continuing in the study. Studies with more than two follow-up phases generally have a high drop-out rate, especially if the participants do not receive a reward that interests them [ 9 , 11 ]. In this study, the drop-out rate was high, representing 63% of the initial sample.…”
Section: Discussionmentioning
confidence: 99%
“…Providing mental health knowledge and promoting health literacy to young university students is a challenge for universities and the public health system [ 7 , 8 ]. Nowadays, an increasing number of cases of young people with depression are undetected, unrecognized and undertreated, leading to tragic episodes such as suicide and causing a great impact on the family and social environment [ 9 , 10 , 11 ]. According to the World Health Organization, depression is the leading cause of disability worldwide [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations